Renewable energy development: How close is the People's Republic of China to achieving carbon neutrality? - Lixia Yao (Asian Development Bank Institute (ADBI), 2024)
Goals to mitigate climate change are to be achieved through government strategies and policies, as well as the availability of low-carbon technologies, and are subject to the underlying institutional, political, economic, and other factors that promote or constrain progress and the path taken. A large CO2 emitter, the People's Republic of China (PRC), has set the goals of carbon dioxide emissions peaking by 2030 and achieving greenhouse gas neutrality by 2060. This study reviews the PRC's efforts to phase out fossil fuels and analyzes the factors that have an impact on the PRC's renewable energy development and its path towards carbon neutrality. Four factors are found to be critical in the decarbonization of the PRC: the costs of retrofitting existing coal-fired power plants and upgrading the power grid to accommodate renewable energy; institutional factors; technology factors; and market-based schemes. Given these factors and the PRC's enormous coal-dependent infrastructure, transitioning away from fossil fuels will be challenging. Another big challenge is the intermittence of renewable energy sources. Hence, the growing penetration of renewable energy in the PRC's electricity mix requires effective policy tools and appropriately designed market signals. To put it simply, the PRC has the potential to develop renewable resources on a large scale, yet it still has a long way to go to achieve carbon neutrality.
Keywords: P28; 330; People's Republic of China; carbon neutrality; fossil fuel phase-out